Facing contemporary slave labor in Brazil: expanding the possibility of labor outsourcing as an obstacle to promotion of decent work policies - Reis da Silva, Lucas (Universidad Nacional del Litoral, 2020)
This article proposes a reflection on the obstacles represented by Brazilian Act n. 13429/2017, which expands the possibility of contracting outsourced labor, to public policies to combat contemporary slave labor by the Brazilian State. The referred law is analyzed in the context of the retrogression of the activities to confront the referred violation that occurred from 2014. It starts from the construction of the concept of contemporary slave labor, from the debates that were built around the theme during this period that begins in the 1980s and which were materialized in the article 149 of the Brazilian Penal Code. Furthermore, the specifics of the concept of contemporary slave labor provided for in Brazilian legislation are juxtaposed to the concepts used by international organizations in order to more precisely delineate the elements that constitute slave labor in Brazil. Thereafter, this article traces a history of confronting the practice of slave labor carried out by the Brazilian State from the moment that it recognized the existence of such a violation in its territory. The present article identified periods of advances and setbacks in the history of combating slave labor in Brazil. Among the setbacks that have been identified, outsourcing presents itself as an element of special importance. First, even before the legislative change that expanded the possibility of outsourcing, it already represented a mechanism used by companies in order to subject workers to conditions of contemporary slavery. Second, because the possibility of outsourcing the core activity, created by the enactment of the aforementioned law, substantially alters the way companies are held accountable for violations in their production chains. Therefore, inserted in this context of setbacks regarding the Brazilian State's action to promote decent work and the elimination of slave labor in its territory, this article analyzes the main effects of the expansion of outsourcing in public policies to combat contemporary slave labor in Brazil.